Public engagement with research reproducibility. - Constant Vinatier; Magdalena Kozula; Veerle Van den Eynden; Laura Caquelin; Hynek Roubik; Inge Stegeman; Florian Naudet (PLoS Biology)
Public engagement with reproducibility is crucial for fostering trust in science. This Community Page outlines, through the example of baking Christmas tree meringues, how scientists can effectively engage and educate the public about the importance of reproducibility in research.